Assessment of Quality and Standards of Technical Education - Deshmukh, S. T. (Journal of Engineering Education Transformations, 2000)
With the modern world of competition, no country or organisation can afford to produce poor quality products. For producing quality products, the human mind is to be utilised in addition to physical skills. It is proved beyond doubt that the human mind has infinite capabilities.